The connection between interoceptive sensitivity and anxiety : the study of temperament’s role in explaining the connection - Tuulos, Titta (2018)
Interoception has important role in many psychological phenomena such as emotional experience. Previous studies suggest that interoception provides a link between biological and psychological processes in many clinically relevant disorders and it has been most frequently connected to various forms of anxiety. Individuals with anxiety tend to be more sensitive to interoception; anxiety is characterized by somatic symptoms and increased attention to autonomic bodily processes supporting a relationship between these variables.